From Usability Testing to Clinical Simulations: Bringing Context into the Design and Evaluation of Usable and Safe Health Information Technologies - Kushniruk, A.; Nohr, C.; Jensen, S.; Borycki, E. M. (Yearbook of Medical Informatics, 2013)
Objectives: The objective of this paper is to explore human factors approaches to understanding the use of health information technology (HIT) by extending usability engineering approaches to include analysis of the impact of clinical context through use of clinical simulations.Methods: Methods discussed are considered on a continuum from traditional laboratory-based usability testing to clinical simulations. Clinical simulations can be conducted in a simulation laboratory and they can also be conducted in real-world settings. The clinical simulation approach attempts to bring the dimension of clinical context into stronger focus. This involves testing of systems with representative users doing representative tasks, in representative settings/environments.Results: Application of methods where realistic clinical scenarios are used to drive the study of users interacting with systems under realistic conditions and settings can lead to identification of problems and issues with systems that may not be detected using traditional usability engineering methods. In conducting such studies, careful consideration is needed in creating ecologically valid test scenarios. The evidence obtained from such evaluation can be used to improve both the usability and safety of HIT. In addition, recent work has shown that clinical simulations, in particular those conducted in-situ, can lead to considerable benefits when compared to the costs of running such studies.Conclusion: In order to bring context of use into the testing of HIT, clinical simulation, involving observing representative users carrying out tasks in representative settings, holds considerable promise.
Keywords: Ussability; clinical simulation; patient safety; technology-induced error; health information systems